Lower urinary tract symptoms and quality of life in community-dwelling individuals aged 45 years and over. A population-based study - Carlos Augusto Faria; Dayse Mary da Silva Correia; Karen Soto Perez Panisset; Maria Luiza Garcia Rosa (Universidade Estadual de Maringá, 2019)
The objective of this study was to identify the factors associated with the impairment of quality of life (QoL) in community-dwelling individuals with LUTS. A randomized sample of the population registered in the Family Health Program - Niterói aged 45 years or over was selected. Information about demographic, socioeconomic and lifestyle factors, co-morbidities and nocturia was collected. The NANDA-I taxonomy was used to identify the other LUTS, and QoL evaluation was performed in accordance with the SF-36 Short Form questionnaire (SF36-SF). For the SF36-SF domains (outcome) associated with LUTS, multiple logistic models were tested including the urinary symptoms and the sociodemographic and associated clinical variables. Stress urinary incontinence was associated with white skin, female gender, obesity, smoking, alcohol intake, depression and low scores in all evaluated domains of QoL. Nocturia was associated with advanced age, low schooling level, higher BMI, hypertension, diabetes, health insurance and the lowest scores in all evaluated domains of Qol, except for the Role Emotional. According to multivariate analysis, stress incontinence and depression are associated with the highest risks of low scores in General Health, Physical Functioning and Vitality domains, while nocturia and obesity showed association with the highest risks of low scores in Physical Functioning, Bodily-Pain and Vitality domains.